2022
DOI: 10.1007/s00702-022-02464-x
|View full text |Cite
|
Sign up to set email alerts
|

Serum neurofilament light chain and postural instability/gait difficulty (PIGD) subtypes of Parkinson’s disease in the MARK-PD study

Abstract: The PIGD (postural instability / gait difficulty) subtype of Parkinson´s disease (PD) is associated with faster cognitive and motor decline. So far, there are no quantifiable biomarkers to aid clinical subtyping. Neurofilament light chain (NfL) is a highly specific marker of neuro-axonal damage and can be assessed in blood. Here, we investigated if serum NfL concentrations are associated with PIGD subtype and PIGD scores in PD patients at advanced disease stages. Furthermore, we evaluated if serum NfL is assoc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
7
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 25 publications
1
7
0
Order By: Relevance
“…These neurochemical and neuropathological findings correlate with a faster motor decline in PIGD patients. In line with these findings, blood NfL was higher in advanced PD patients with the PIGD subtype independent of age, sex and disease duration in a single-centre in Singapore and in the MARK-PD study from Hamburg (Ng et al 2020;Potter-Nerger et al 2022). However, baseline blood NfL levels did not differ between PIGD and TD subtypes at early disease stages, i.e.…”
Section: Blood Nfl and Parkinson Subtypessupporting
confidence: 74%
“…These neurochemical and neuropathological findings correlate with a faster motor decline in PIGD patients. In line with these findings, blood NfL was higher in advanced PD patients with the PIGD subtype independent of age, sex and disease duration in a single-centre in Singapore and in the MARK-PD study from Hamburg (Ng et al 2020;Potter-Nerger et al 2022). However, baseline blood NfL levels did not differ between PIGD and TD subtypes at early disease stages, i.e.…”
Section: Blood Nfl and Parkinson Subtypessupporting
confidence: 74%
“…Moreover, the diffuse malignant phenotype was associated with a higher extent of atrophy in cerebral magnet resonance imaging (Fereshtehnejad et al 2017 ). The authors of a recent German study reported that serum NLF levels were increased in the PIGD subgroup and that NFL levels significantly correlated with the Montreal cognitive assessment (MoCA) scale and the MDS-UPDRS part III in PIGD patients (Pötter-Nerger et al 2022 ), emphasizing the diagnostic value of this biomarker.…”
Section: Diagnostic and Pathophysiological Aspects Of Parkinson’s Dis...mentioning
confidence: 99%
“…Blood NfL was also found associated with PIGD-subtype of PD (Pötter-Nerger et al 2022 ; Ng et al 2020 ). At 2 year follow-up, NfL levels were higher in PIGD compared to tremor-dominant subtype, and within the PIGD group, higher blood NfL was associated with worse global cognition and UPDRS III at baseline and predicted motor and cognitive decline (Ng et al 2020 ).…”
Section: Blood-based Biomarkermentioning
confidence: 99%